Contributing Factors of Smart Village Implementation in Rural Area: A Systematic Literature Review - Suprapti, Suprapti; Nugroho, Rino Ardhian; Prakoso, Septyanto Galan (Publik : (Jurnal Ilmu Administrasi), 2025)
This study aims to analyze what factors support the successful implementation of Smart Villages in rural Indonesia. The research method used was a systematic literature review (SLR), by analyzing 16 selected articles from the Scopus database using strict inclusion-exclusion criteria and the PRISMA procedure. The results of the study show that five main factors drive the success of Smart Villages, namely: the provision of digital technology and infrastructure, social participation and the improvement of people's digital literacy, village digital economy transformation, leadership and adaptive governance, as well as sustainability characteristics such as precision agriculture, renewable energy, sharing economy, and social innovation. The discussion emphasized that smart village development must be based on multi-actor collaboration with a technological approach tailored to the local context. The conclusion of this study is that the success of Smart Villages depends on a combination of technological, social, economic, and institutional factors. However, the limitations of this study lie in the non-use of primary field data and the limited sources of literature in Indonesian. For further research, it is recommended to conduct field studies in various village contexts, as well as the development of integrative models that combine social, cultural, and technological approaches to support the sustainability of Smart Villages.